KEKEBALAN BEBERAPA STRAIN IKAN MAS (Cyprinus carpio) TERHADAP INFEKSI Aeromonas hydrophila - , NUR HASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research was to determine LD50 value and comparison immunity of common carp strains against A. hydrophila bacteria. This research was conducted on Completely Randomized Design (CRD) composed by 4 treatments common carp strains and 5 dose injection A. hydrophila in duplo. Common carp strains used were Cangkringan, Majalaya, crossed Cangkringan with Koi and crossed Rajadanu with Koi. Injection dose were 0 cfu/ml, 104 cfu/ml, 105 cfu/ml, 106 cfu/ml and 107 cfu/ml. The infection A. hydrophila bacteria to common carp administered by intraperitoneal injection 0,1 ml/fish. The parameters evaluated were daily mortality and clinical symptoms. The result of LD50 value common carp strains against A. hydrophila were 10.07 x 105 cfu/fish for Cangkringan, 5.22 x 105 cfu/fish for crossed Koi with Cangkringan, 4.19 x 105 cfu/fish crossed Koi with Rajadanu and 7.01 x 105 cfu/fish for Majalaya. Based on analyzed by analysis of varians so differential strains did not effect on common carp immunity against A. hydrophila infection (P > 0.05).